If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3b + -1b(-3) + 3(-1b) = 0 Reorder the terms for easier multiplication: 3b + -1 * -3b + 3(-1b) = 0 Multiply -1 * -3 3b + 3b + 3(-1b) = 0 Remove parenthesis around (-1b) 3b + 3b + 3 * -1b = 0 Multiply 3 * -1 3b + 3b + -3b = 0 Combine like terms: 3b + 3b = 6b 6b + -3b = 0 Combine like terms: 6b + -3b = 3b 3b = 0 Solving 3b = 0 Solving for variable 'b'. Move all terms containing b to the left, all other terms to the right. Divide each side by '3'. b = 0 Simplifying b = 0
| 3X-21=4X-36 | | Ln*(x-4)+ln*(x-7)=ln*18 | | 3xb-bx(-3)+3x(-b)= | | 1/3k-1=4/6 | | In*(x-6)+In*(x-4)=In*15 | | 6x-9-4x=13 | | (4y+7)(4-y)=0 | | q(z)=pz+b | | ln*(x-5)+ln*(x-8)=ln*28 | | x-1/5=3-(x-9)/2 | | (150-80/1-x)2x=0 | | 40-(5)x=8+x | | (5-3x)2x=0 | | (4g-2)*(4g-2)=4 | | 3(2m-8)-4m=20 | | 2sinx=5+cosx | | 4.5=4t^2 | | 7x^2+7x=9 | | cos7x=cosx/3 | | 11-4+(-1)*5= | | 9t+18-3t-15= | | y=2x^4-4x^2+15 | | 2(2x-1)-3(x+3)=x+1 | | 7y+8y-3x-4x= | | 2x-25+7x-75=7x-20 | | 7x-x^3=6 | | 9x+3y-6x+2y= | | 4w+10=-3(w-8) | | 25x+7x-4x-6x= | | Sinx=-.72 | | 2(d+6)=-2d-12 | | X+40+y=180 |